Maternal & fetal outcome of hypertensive disorders of pregnancy - a study of 100 cases, in FMCH, Faridpur - Saha, MR; Khan, JH (Journal of Dhaka Medical College, 2012)
DOI: http://dx.doi.org/10.3329/jdmc.v20i2.10547 J. Dhaka Med. Coll. 2011; 20(2): 183-187